Singing the Body: Postmodern Orality and the Female Body in the Nigerian Hip Hop Nation. - Olusegun-Joseph, Yomi (Contemporary Music Review, 2020)
The current trend in the Nigerian Hip Hop Nation (NHHN) to transgress established socio-cultural codes of 'adult-run society' in the Nigerian nation state has become a phenomenal postmodern signifier of urban youth difference. While this development has been acknowledged in a number of academic submissions, there has however been a dearth of scholarship to account for the temporal socio-economic/cultural imperatives that have shaped it, and how these motivations have impacted new youth identity formations, intra-NHHN power relations and the remapping of gender. Recognising Nigerian hip hop as predominantly framed around a male entertainment orientation and counterhegemonic cultural outlook, this paper argues that the present-day circulation of hip hop in Nigeria is a deconstructive, transcultural, and capitalist practice that presents an arena of youth self-(re)encounter, especially in the area of an overwhelming politics of masculinity, rethinking nation/belonging and the discursive (re)drawing of the female body. In this context, I suggest that the representation/performance of the female body in the NHHN, quite against popular notions of its vulnerability to misogyny, revolves around a site of ambivalence in which woman is both visible and discursively veiled, claiming agency within a dominantly hyper-masculinist youth (sub)culture as much as getting objectified in it. In this context, it is difficult to posit a case of 'Nigerian feminist hip hop' within a definitive space of black sisterhood and this requires critical contemplation.